2013
DOI: 10.1186/1472-6963-13-509
|View full text |Cite
|
Sign up to set email alerts
|

Health examination utilization in the visually disabled population in Taiwan: a nationwide population-based study

Abstract: BackgroundPeople with visual disabilities have increased health needs but face worse inequity to preventive health examinations. To date, only a few nationwide studies have analyzed the utilization of preventive adult health examinations by the visually disabled population. The aim of this study was to investigate the utilization of health examinations by the visually disabled population, and analyze the factors associated with the utilization.MethodsVisual disability was certified by ophthalmologists and auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…La falta de información en salud y la insatisfacción usuaria de esta población sumado a la falta de capacitación y concientización del personal sanitario acarrean varios problemas para las PcD sensorial. Lo anterior, implica un desconocimiento de su propio estado de salud, los tratamientos o cuidados a seguir, un menor uso de los servicios de salud en los distintos niveles de prevención y en sus distintas áreas, lo que generaría una mayor incidencia de comorbilidades y un mayor gasto en salud 10,55,57,80,95 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La falta de información en salud y la insatisfacción usuaria de esta población sumado a la falta de capacitación y concientización del personal sanitario acarrean varios problemas para las PcD sensorial. Lo anterior, implica un desconocimiento de su propio estado de salud, los tratamientos o cuidados a seguir, un menor uso de los servicios de salud en los distintos niveles de prevención y en sus distintas áreas, lo que generaría una mayor incidencia de comorbilidades y un mayor gasto en salud 10,55,57,80,95 .…”
Section: Discussionunclassified
“…De acuerdo a datos de Taiwán, la utilización general del examen de salud ofrecido solo alcanza al 16% de las PcD visual 10 , en los Estados Unidos de Norteamérica las PcD visual son más propensas a no poseer una fuente de cuidado habitual y experimentan mayores necesidades insatisfechas en referencia a sus contrapartes con otra discapacidad 56 .…”
Section: Acceso a Atención Sanitariaunclassified
See 1 more Smart Citation
“…Our study illustrates the severity of visual impairment is a significant factor as utilization of barrier in Pap smear screening test [ 14 ] indicated the utilization of preventive health service in people with visual impairment is also lower with the severity of disabilities (from 19.16 to 2 %) [ 14 ]. And the other survey found that the utilization of Pap smear screening test in women with disabilities also decreases with the severity of disabilities (from 10.19 to 5.47 %) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with schizophrenia also have less access to health examinations or screening check-ups. Under the NHI program in Taiwan, the utilization rate of health examinations by the severely mentally ill was 22.32% [ 34 ], while the rate in the general population was 33.3 to 46.8% [ 35 ]. Healthcare disparity for patients with schizophrenia seems to be multi-dimensional, and the medical community should collectively take the initiatives to improve it.…”
Section: Discussionmentioning
confidence: 99%